Management Strategies and Outcomes of ST‐Segment Elevation Myocardial Infarction Patients Transferred After Receiving Fibrinolytic Therapy in the United States. Issue 1 (19th January 2016) - Patel, Nish; Patel, Nileshkumar J.; Thakkar, Badal; Singh, Vikas; Arora, Shilpkumar; Patel, Nilay; Savani, Chirag; Deshmukh, Abhishek; Thadani, Udho; Badheka, Apurva O.; Alfonso, Carlos; Fonarow, Gregg C.; et al.
ABSTRACT: Fibrinolytic therapy is still used in patients with ST‐segment elevation myocardial infarction (STEMI) when the primary percutaneous coronary intervention cannot be provided in a timely fashion. Management strategies and outcomes in transferred fibrinolytic‐treated STEMI patients have not been well assessed in real‐world settings. Using the Nationwide Inpatient Sample from 2008 to 2012, we identified 18 814 patients with STEMI who received fibrinolytic therapy and were transferred to a different facility within 24 hours. The primary outcome was in‐hospital mortality. Secondary outcomes included gastrointestinal bleeding, bleeding requiring transfusion, intracranial hemorrhage (ICH), length of stay, and cost. The patients were divided into 3 groups: those who received medical therapy alone (n = 853; 4.5%), those who underwent coronary artery angiography without revascularization (n = 2573; 13.7%), and those who underwent coronary artery angiography with revascularization (n = 15 388; 81.8%). Rates of in‐hospital mortality among the groups were 20% vs 6.6% vs 2.1%, respectively ( P < 0.001); ICH was 8.5% vs 1.1% vs 0.6%, respectively ( P < 0.001); and gastrointestinal bleeding was 1.1% vs 0.4% vs 0.4%, respectively ( P = 0.011). Multivariate analysis identified increasing age, higher Charlson Comorbidity Index score, cardiogenic shock, cardiac arrest, and ICH as the independent predictors of not performing coronary artery angiography and/or revascularization in patients with STEMI initially treated with fibrinolytic therapy. The majority of STEMI patients transferred after receiving fibrinolytic therapy undergo coronary angiography. However, notable numbers of patients do not receive revascularization, especially patients with cardiogenic shock and following a cardiac arrest.